Analysis of take-off executions of top athletes in ski jumping - Müller, S.; Kreibich, S.; Seidel, I. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: In ski jumping the take-off is a key position within the entire movement. The execution of take-off and the jump intensity (vertical take-off velocity) have a direct impact on the take-in of the flight posture and of the flight distance. Due to the changes in the materials (jump suits, ties, shoes) but also the use of standardized (ice) track systems realize the best athletes in the inrun position and in take-off an ever-increasing submission of the center of gravity (Müller, Kreibich & Wiese, 2014). In the analysis of the take-off-execution interested the question of how the action of force under these conditions, and whether there are differences between the top athletes.